Efektivitas Model Pembelajaran Generatif Terhadap Keterampilan Generik Sains Fisika Peserta Didik Pada Materi Momentum Dan Impuls - Sudirman, Sudirman (Al-Khazini, 2022)
Generic learning of physics science students taught using generative learning models, learning generic science skills of students physics taught without using generative learning models, learning the effectiveness of using generative learning models in increasing generic physics science assistance. This type of research used in this study is a quasi-experimental type of research with the research design The Matching only post Test Group Design. The population of this research is all students of class X TKJ. The sampling technique used was convenience sampling.The results shows that the generic science skills of students in class X TKJ show that the average value of the experimental class (X TKJ 2) is 75.80. As for the control class the average value obtained was 72.52. The results of hypothesis testing using independent sample T-2 test obtained t count = 1.34 and t table = 2.00. As a result it can be seen that t count <t table, so it can be concluded that H0 is accepted and H1 is rejected. Thus, there is no influence between the class being taught using generative learning models and the classes being taught without using the generative learning model. This means that the generative learning model is not effectively used in class X TKJ